Clinical evaluation of the effectiveness of electrophoresis with a periodontal gel composition based on a flavonoid complex under the conditions of stress-modulating effect of fixed orthodontic appliances on periodontal tissues - Hodovanyi, O. V. (Actual Dentistry, 2023)
Introduction. One of the most important biological reactions to orthodontic treatment with braces is oxidative stress, which in patients with periodontal diseases is associated with a number of proinflammatory factors and hypoxia. The development of effective treatment regimens to eliminate the effects of local oxidative stress and the use of adequate prognostic markers for its regulation is an important promising area in the treatment of orthodontic patients with periodontal tissue diseases. The aim of this study was to evaluate the clinical efficacy of the developed therapeutic and prophylactic complex, which included a modified procedure of gingival electrophoresis in combination with the periodontal gel composition “Benzidaflaziverdinе” (GCB), consisting of two active components—flavonoid complex and benzidamine hydrochloride in the treatment of chronic generalized periodontitis(CGP) of initial-I degree of severityin orthodontic patients before and during the active period of orthodontic treatment under conditions of local oxidative stress. Materials and methods. The subject of this study were 118 patients aged 20-35 years, diagnosed with various types of dentoalveolar anomalies against the background of initial-I stage CGP, divided into two groups. In patients of the main group (60 people), the developed treatment and prophylactic complex with modified gingival electrophoresis and GCB was used before the active period of orthodontic treatment and during its course (3 and 6 months). Patients in the comparison group (58 people) received a traditional treatment regimen, including applications with Cholisal gel, within the same time frame. To assess the effectiveness of the treatment, the BOP, API and GI indices were calculated. The value of lactate dehydrogenase (LDH) in saliva was used as a prognostic marker of local oxidative stress. Results. The inclusion of the electrophoresis procedure in combination with GCB in the complex of therapeutic and preventive measures before and during the active period of orthodontic treatment in patients of the main group led to a more intensive normalisation of BOP, API, GI and LDH levels. There was a faster improvement in the condition of periodontal tissues which ensured a favourable course of the active period of orthodontic treatment. In the main group, 3 months after the start of orthodontic treatment, there was a minimal increase in the BOP (7.85±3.18%), ARI (11.13±10.12%) and GI (0.07±0.05 points) indices, which indicated a slight destabilisation of the situation, which required only minor correction. At the same time, patients in the comparison group showed an active increase in index parameters – BOP (43.48±23.12%), API (70.64±17.98%) and GI (0.59±0.33 points), which confirmed the loss of remission and required a second course of treatment with a traditional regimen. If after the installation of braces in the main group, the LDH index was within 424.52±103.5 units/l (p<0.001), then in the comparison group this led to a sharp increase to 1687.6±240.8 units/l, which to a certain extent exceeded the index of the same comparison group before periodontal treatment (1446.1±441 units/l) and indicated the presence of a significant local stress-modulating reaction and insufficient effectiveness of the traditional treatment regimen. Conclusions. According to the results of changes in periodontal status and LDH indices in orthodontic patients with CGP, it is possible to note the expediency of using the developed GCB in combination with electrophoresis in the tissues of the periodontal complex before and during active orthodontic treatment. The clinical efficacy of the proposed treatment and prophylactic complex was confirmed by the BOP, API and GI indices. The studies also suggested that the level of LDH is a sensitive marker that reflects the biological activity that occurs in the periodontium in the case of CGP before periodontal treatment and during the first three months of orthodontic movement of teeth. Therefore, this enzyme can be used as a diagnostic tool for monitoring orthodontic treatment in patients with periodontal tissue pathology.